Improving questionnaire reliability using construct reliability for researches in educational technology - Rosli, Mohd Shafie; Saleh, Nor Shela; Alshammari, Sultan Hammad; Ibrahim, Mohd Mokhzani; Atan, Azri Syazwan; Atan, Noor Azean (2021)
This paper is exploring on maneuver to improve research instrument reliability in scientific research related to Educational Technology by analyzing the traditional Cronbach’s alpha reliability using SPSS software and the newer statistical tool, AMOS using Construct Reliability (CR) approach. Two sets of data were used as sample to perform the comparison. The first set of data is from a research involving Technology Enhanced Learning Environment. The second data are sampled from research in digital competency. Finding from this paper concluded that, conventional approach of using Cronbach’s alpha have lower reliability than the newer approach of using CR. Using Cronbach’s alpha show tendency toward measuring consistency instead of reliability. CR offer better definition of reliability and give a robust measurement of reliability in research. This paper had shed light into offering alternative approach to the commonly and widely uses of research reliability especially when it involves questionnaire as instrument.